Analisis Load Sharing dan Load Shedding Operasi Paralel Generator Singkron PG Kebun Agung - Epiwardi; Rachmat Sucipto; Tresna Umar Syamsuri (Elposys: Jurnal Sistem Kelistrikan, 2023)
The Kebon Agung sugar factory has two power supplies, namely from the PLTU Kebon Agung sugar factory itself and from PLN. There are 3 synchronized generators at the Kebun Agung Sugar Factory, with a power of 4.5 MW on generators 1,2 and 1,6 MVA on generator 3. The difference in power between generators 1,2 and 3 causes frequent interference with generator 3 because it has less power. This Final Project analyzes load sharing and load shedding using MATLAB Simulink R2013a. Through these simulations it is shown the division of the load from each generator during normal conditions or when one generator is released. see the effect of the generator that has been set to speed droop when load sharing conditions, the speed of droop is varied so that it knows the characteristics of the generator that has been set speed droop. In the Final Project, the simulation value and calculation of the speed droop setting value in the Kebon Agung sugar factory is ideal. Because ideally the setting of speed droop in the settings so it is not too sensitive and not too long in responding to changes in load that occur in the system.